Educomunicação: interfaces entre televisão e educação - Valério, Ana Cláudia (2012)
This research aims to study the associations between communication and education, from the perspective of Educommunication, stopping at the educational process, inherent in television. Since this is a theoretical study, the methodology is closely related to the theoretical, since no object of this investigation was a case study. As a theoretical research and literature, the authors discussed that address the interfaces between education and television, with a view to training citizens more critical. Initially an investigation was undertaken for the production of academic knowledge in the area, important for understanding. A search in the databases of theses and dissertations from Brazilian universities and the Lattes Platform. From this, it was found that most of the work with the theme Educommunication is present in the Center for Communication and Education (NCE), the School of Communication and Arts (ECA) at the University of São Paulo (USP). This is because the founder of the NCE, Professor Ismar de Oliveira Soares, in Brazil it is a precursor of research in the area.Thus, this work shows the existence of Educommunication with a new field of knowledge, independent, that is consolidating from discussions undertaken both by scholars and researchers, for teachers and communicators. Accordingly, we assessed authors of the areas of education and communication, that before the consolidation of the term Educommunication already discussed this relationship, both nationally and internationally, and helped with their practices and research to provide theoretical support to this new perspective. Moreover, the emergence of an analysis of this fact, increasingly permeated by new technologies and the media has highlighted the need to discuss more forcefully the relationship between the fields of education and communication. After all, this society has mediated new forms of relationship and promotes change in all social institutions. And in this context, television is seen as the main element of socialization, being the main source of information and entertainment for millions of Brazilians, since much of the population is informed, educated and is distracted by television. The ways of talking, acting and understanding the world televised reach all segments of society, including the school, which must learn to deal with this reality. If educational television, why not use it as a teaching, bringing their language, their programming, their ways of seduction to the classroom? The school should promote education for the media so that citizens have a more critical understanding of reality. We consider this work to education in a broad sense, comprising all the experiences through which the human being passes in all its relations. Thus, we analyzed the relationship between television and education, unveiling the mechanisms of seduction used and the elements of which the TV is appropriated to build their language, and discussing the educational potential of the medium, in both formal and informal.